2016
DOI: 10.1099/jmmcr.0.005041
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium baratii: a rare case of pneumonia associated with an Alzheimer patient in Rio de Janeiro, Brazil

Abstract: Introduction: Clostridium baratii is rarely associated with human diseases. Infection is usuallcaused by ingestion of contaminated food, and infant botulism is the most common clinical presentation.Case Report:Here we report a case of pneumonia by a non-toxigenic strain of C. baratii in an Alzheimer 70-year-old male with sepsis in Rio de Janeiro, Brazil. The micro-organism was identified by phenotypical tests, mass spectrometry (MALDI-TOF), DNA amplification (PCR) and sequencing of the 16S rRNA gene. Testing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…C. baratii is not taxonomically related to C. botulinum, but some members of this species have caused Microorganisms 2022, 10, 213 2 of 17 botulism outbreaks associated with food consumption, as well as sporadic infant botulism cases (less than 1% of total cases). These outbreaks are described as sporadic and rare episodes [11][12][13][14][15]; however, the strains that possess the neurotoxin may pose a significant threat, and it is essential to further study the properties of these microorganisms. C. baratii strains have been found in liver pastes, meat, soil, and other foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. baratii is not taxonomically related to C. botulinum, but some members of this species have caused Microorganisms 2022, 10, 213 2 of 17 botulism outbreaks associated with food consumption, as well as sporadic infant botulism cases (less than 1% of total cases). These outbreaks are described as sporadic and rare episodes [11][12][13][14][15]; however, the strains that possess the neurotoxin may pose a significant threat, and it is essential to further study the properties of these microorganisms. C. baratii strains have been found in liver pastes, meat, soil, and other foods.…”
Section: Introductionmentioning
confidence: 99%
“…There are eight serotypes of BoNT toxins (A-G, and X) [16], which differ in their protein targets [17]. The C. baratii isolates responsible for the outbreaks have been shown to carry the botulinum neurotoxin (BoNT) and its gene cluster responsible for the production of the Type F botulinum toxin [12][13][14][15][16][18][19][20][21][22][23]. The F serotype is generally produced by C. botulinum strains and some strains of C. baratii.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of this species to our original choices of antibiotics led the infectious disease service to choose a combination of carbapenems and metronidazole. Our successful antimicrobial regimen is supported by other studies that utilize combination therapy to treat Clostridium species that cause septicemia in patients infected with Clostridium subterminale [ [5] , [6] , [7] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 70%
“…Identification of Clostridium baratii is also an unusual finding. Lima et al reported a rare case presenting as a severe pneumonia in a patient with Alzheimer’s disease [ 10 ]. The isolation of this species may not be surprising since diseased teeth and periodontal tissue have been implicated in anaerobic pleuropulmonary infections [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation